Insights Into Protein S-Palmitoylation in Synaptic Plasticity and Neurological Disorders: Potential and Limitations of Methods for Detection and Analysis - Zaręba-Kozioł, Monika; Figiel, Izabela; Bartkowiak-Kaczmarek, Anna; Włodarczyk, Jakub (Frontiers in Molecular Neuroscience, 2018)
S-palmitoylation (S-PALM) is a lipid modification that involves the linkage of a fatty acid chain to cysteine residues of the substrate protein. This common posttranslational modification (PTM) is unique among other lipid modifications because of its reversibility. Hence, like phosphorylation or ubiquitination, it can act as a switch that modulates various important physiological pathways within the cell. Numerous studies revealed that S-PALM plays a crucial role in protein trafficking and function throughout the nervous system. Notably, the dynamic turnover of palmitate on proteins at the synapse may provide a key mechanism for rapidly changing synaptic strength. Indeed, palmitate cycling on postsynaptic density-95 (PSD-95), the major postsynaptic density protein at excitatory synapses, regulates the number of synaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) and thus affects synaptic transmission. Accumulating evidence suggests a relationship between impairments in S-PALM and severe neurological disorders. Therefore, determining the precise levels of S-PALM may be essential for understanding the ways in which this PTM is regulated in the brain and controls synaptic dynamics. Protein S-PALM can be characterized using metabolic labeling methods and biochemical tools. Both approaches are discussed herein in the context of specific methods and their advantages and disadvantages. This review clearly shows progress in the field, which has led to the development of new, more sensitive techniques that enable the detection of palmitoylated proteins and allow predictions of potential palmitate binding sites. Unfortunately, one significant limitation of these approaches continues to be the inability to use them in living cells.